CEO inside debt and corporate debt maturity structure - Dang, Viet A.; Phan, Hieu V. (Journal of Banking & Finance, 2016)
This paper examines the relation between chief executive officer (CEO) inside debt holdings and corporate debt maturity. We provide robust evidence that inside debt has a positive effect on short-maturity debt and that this effect is concentrated in financially unconstrained firms that face lower refinancing risk. Our analysis further shows that CEO inside debt helps reduce the cost of debt financing. Overall, our results indicate that managerial holdings of inside debt facilitate access to external debt financing and reduce refinancing risk, thus incentivizing managers to use less costly shorter term debt.